ANALISIS KINERJA PEGAWAI NEGERI SIPIL DI KANTOR KECAMATAN TEMBALANG KOTA SEMARANG - Manurung, Herawaty; Nurcahyanto, Herbasuki; Hariani, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Employee performance is the result or output obtained from each employee who works at the institution. In this study . This research relates to employee performance analysis in Sub-district Office Tembalang, Semarang city, is cheks relationship between employee capability, employee discipline, employee motivation with employee performance. Sample is taken by using the method of sampling techniques jenuh/sensus. Sampling jenuh is used when population in a relatively small in amount or less than 30 people, so that all members of the sample population is used as much as people. Technical analysis is a technique used Rank analysis of Kendall and Kendall's Concordance, which is used to determine whether there is a relationship between variables, and the results of analysis to prove:1. Correlation between employee capability variable with employee performance variable showed a correlation coefficient of 0,219 with a significant level of 0,103 > 0,05 which means there is not significant relationship between employee capability with employee performance.2. Correlation between employee discipline variable with employee performance variable showed a correlation coefficient of 0,332 with a significant level of 0,015 < 0,05 which means there is a significant relationship between employee discipline with employee performance3. Correlation between employee motivation variable with employee performance variable showed a correlation coefficient of 0,262 with a significant level of 0,049 < 0,05 which means there is a significant relationship between employee motivation with employee performance.4. Correlation between employee capability variable, employee discipline variable, employee motivation variable with employee performance concurrently having a significant relationship, it is retrieved from the result chi-square of 66,101.